Effectiveness of a web-based decision aid for patients with Generalised Anxiety Disorder in Spain: a randomised controlled trial - Lilisbeth Perestelo-Pérez; Amado Rivero-Santana; Yolanda Álvarez-Pérez; Andrea Duarte-Díaz; Himar Gonzalez-Pacheco; Anthea Santos-Álvarez; Wenceslao Peñate-Castro; Vanesa Ramos García; María del Mar Trujillo-Martín; María Isabel Del Cura-González (BMJ Health & Care Informatics)
Objective To evaluate the effectiveness of an online Patient Decision Aid (PtDA) for patients with Generalised Anxiety Disorder (GAD).Design Randomised controlled trial comparing the PtDA to general information (fact sheet).Setting The study took place in 17 primary care centres in the Canary Islands (Spain).Participants Patients diagnosed with GAD and a score ≥8 in the GAD-7 questionnaire.Intervention Patients were randomly allocated to the PtDA group (n=58) or the control group (n=61).Main outcome measure The primary outcome was decisional conflict at postintervention, assessed with the Decisional Conflict Scale (DCS). Secondary outcomes include knowledge about GAD and its treatments, concordance between informed preference and 3 month actual choice, decision quality and GAD symptoms.Results There were no significant differences in decisional conflict at postintervention or 3 month follow-up in the intention-to-treat (ITT) or per-protocol sample (PPS). The PtDA significantly improved postintervention (MD=1.65, 95% CI: 0.84 to 2.46) and 3 month objective knowledge (MD=0.78, 95% CI: 0.02 to 1.55). In the PPS, anxiety symptoms at 3 months were significantly lower in the PtDA group (MD=−3.00, 95% CI: −5.69 to –0.30), but in the ITT sample, this difference did not reach significance (p=0.06). There were no significant differences in the rate of patients unsure about treatment preference at postintervention, nor on concordance or decision quality at follow-up.Conclusion The use of the PtDA led to improvements in knowledge at 3 months, but it did not result in a significant reduction of decisional conflict. These results must be interpreted with caution, given the methodological limitations of the study, mainly the high rate of dropouts. Further research is needed to confirm these results, the first published on the effectiveness of a PtDA for GAD patients.Trial registration number NCT04364958.